Antitumor Activity of Combination Therapy with Metformin and Trametinib in Non-Small Cell Lung Cancer Cells - Ko, Eunjeong (Dev Reprod, 2020)
Metformin has been widely used as an antidiabetic drug, and reported to inhibit cell proliferation in many cancers including non-small cell lung cancer (NSCLC). In NSCLC cells, metformin suppresses PI3K/AKT/mTOR signaling pathway, but effect of metformin on RAS/ RAF/MEK/ERK signaling pathway is controversial; several studies showed the inhibition of ERK activity, while others demonstrated the activation of ERK in response to metformin exposure. Metformin-induced activation of ERK is therapeutically important, since metformin could enhance cell proliferation through RAS/RAF/MEK/ERK pathway and lead to impairment of its anticancer activity suppressing PI3K/AKT/mTOR pathway, requiring blockade of both signaling pathways for more efficient antitumor effect. The present study tested the combination therapy of metformin and trametinib by monitoring the alterations of regulatory effector proteins of cell signaling pathways and the effect of the combination on cell viability in NCI-H2087 NSCLC cells with NRAS and BRAF mutations. We show that metformin alone blocks PI3K/AKT/mTOR signaling pathway but induces the activation and phosphorylation of ERK. The combination therapy synergistically decreased cell viability in treatment with low doses of two drugs, while it gave antagonistic effect with high doses. These findings suggest that the efficacy of metformin and trametinib combination therapy may depend on the alteration of ERK activity induced by metformin and specific cellular context of cancer cells.